Safety design analysis of a vent mast on a LNG powered ship during a low-temperature combustible gas leakage accident - Yu Cao; Qiao-jiao Jia; Shi-ming Wang; Yong Jiang; Yong Bai (Journal of Ocean Engineering and Science, 2022)
Liquefied natural gas (LNG) is a kind of clean energy, and many LNG-powered vessels have been designed and built around the world. However, LNG introduces the potential risk of leakage and explosion accidents; thus, it is necessary to conduct safety assessments on the layout of typical facilities during the initial design stage. In this paper, an on-deck LNG fuel area model is established by employing the computational fluid dynamics (CFD) method according to an LNG-powered Aframax oil tanker. The distribution of potential dangerous areas on the concentration field and temperature field is presented under leakage and diffusion accident conditions with vent masts of different heights. The results show the following: the gas concentration rises rapidly at the initial stage of leakage and tends to stabilize after a certain period; the leakage and diffusion trend of light gas is basically the same as that of heavy gas, and the lowest heavy gas and light gas temperature on the deck between the storage tank and the upper building is -7.9 C and 4.7 °C, respectively, when the venting mast leakage point is at the height of 6 m; and the higher the mast leakage point is, the more safe the ship design. For safety considerations, the height of the venting mast designed in this paper should not be lower than the height of the LNG storage tank, which is 10 m.